2002
DOI: 10.1302/0301-620x.84b4.12434
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of anabolic steroids, vitamin D and calcium on muscle mass, bone mineral density and clinical function after a hip fracture: A randomised study of 63 women

Abstract: A total of 63 women who had an operation for a fracture of the hip was randomly allocated to one year of treatment either with anabolic steroids, vitamin D and calcium (anabolic group) or with calcium only (control group). The thigh muscle volume was measured by quantitative CT. The bone mineral density of the hip, femur and tibia was assessed by quantitative CT and dual-energy x-ray absorptiometry and of the heel by quantitative ultrasound. Quantitative CT showed that the anabolic group did not lose muscle vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 77 publications
(82 reference statements)
0
24
1
2
Order By: Relevance
“…The impact of vitamin D on falls might be explained by the improvement in musculoskeletal function. Hedstrom et al 36 also observed that treatment with vitamin D and calcium had a beneficial effect on muscle volume, bone mineral density and clinical function. We believe that these data on the relationship between fatty degeneration of muscles of the rotator cuff and the serum level of vitamin D are important in that tears of the cuff particularly afflict the elderly, and the prevalence of low vitamin D levels is considerably higher in that age group.…”
Section: Discussionmentioning
confidence: 96%
“…The impact of vitamin D on falls might be explained by the improvement in musculoskeletal function. Hedstrom et al 36 also observed that treatment with vitamin D and calcium had a beneficial effect on muscle volume, bone mineral density and clinical function. We believe that these data on the relationship between fatty degeneration of muscles of the rotator cuff and the serum level of vitamin D are important in that tears of the cuff particularly afflict the elderly, and the prevalence of low vitamin D levels is considerably higher in that age group.…”
Section: Discussionmentioning
confidence: 96%
“…In one, four weeks of weekly injections had no effect (113). In the other, nandrolone, administered to a mixed population of hip fracture patients every three weeks for one year, resulted in retained muscle volume in the injured leg as compared to the control group (57). Moreover, this study by Hedström et al showed that hip function and gait speed were better in the nandrolone-treated group.…”
Section: Nutritional Assessment and Anabolic Interventionmentioning
confidence: 77%
“…anabolic steroids, testosterone and growth hormone, have been tested in widely varying clinical conditions and may be beneficial (54)(55)(56). For example, nandrolone administered for one year to hip fracture patients reduced the wasting of muscle and bone and improved hip function (57).…”
Section: Nutritional Assessment and Anabolic Interventionmentioning
confidence: 99%
“…However, in clinical applications, AASs appear to have a favorable anabolic effect on patients with chronic diseases and muscle catabolism and on loss of muscle mass in the elderly (i.e., sarcopenia;Evans, 2004;Hoffman & Ratamess, 2006;Kicman, 2008;Orr & Fiatarone Singh, 2004). The appropriate use of AASs during rehabilitation has been reported to have beneficial effects, such as an increase in lean body mass, muscle strength, or physical activities for patients with hip fracture (Hedstrom et al, 2002), chronic obstructive pulmonary disease (Ferreira et al, 1998), and severe burn injury (Demling & De-Santi, 2001), especially when combined with exercise (Miller & Btaiche, 2008;Sharma et al, 2008). However, to our knowledge, there have been no investigations of the effects of AASs on stroke patients with muscle weakness.…”
Section: Introductionmentioning
confidence: 99%